Low Complexity Sub-Optimal Transmit Antenna Selection Schemes for Spatial Modulation - Shivendra Mishra, Asha S, Vishnu Vardhan Gudla, Vinoth Babu Kumaravelu, Arthi Murugadass (International Journal of Advanced Science and Technology, 2020)
The main objective of this work is to employ low complexity transmit antenna selection schemes, which improves the system performance compared to conventional Spatial Modulation (SM) without antenna selection. To attain transmit diversity, antenna selection schemes are employed to SM. Antenna selection metrics such as channel amplitude, channel correlation between transmit antennas and their combination are used. In this paper, three different sub-optimal schemes based on the above metrics is employed for SM. It is observed that antenna selection based on channel amplitude and correlation scheme for SM (AS-CA-C-SM) outperforms the other two schemes, but with increased complexity compared to the scheme using only channel amplitude (AS-CA-SM). For all the schemes, it is observed that the increase in the number of available antennas increases the antenna selection gain.